Coconut aqueous processing - Apostol, Avelyn M. (College of Engineering, 1985)
This plant design project evaluated the feasibility of employing the aqueous processing of coconuts in medium-scale operations. Using a capacity of 25 MT white endosperm per day, the end-products are natural oil, expelled oil, protein powder and vinegar. A total capital investment of P 171,137,324 is required for this venture. Basing product prices on prevailing rates, and for new products, on the prices of the most similar existing commodity (if no price estimate is given for that particular product), a 6.16% ROI after taxes is realized. The break-even point is at 29.1% of the maximum production, and the pay-out time is 7.1 years.